â€œMOVEâ€ ANALYSIS IN CLASSROOM INTERACTION (An Functional Grammar Approach - Shalehoddin, Shalehoddin; Ashari, Erwin (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2016)
Find out the form of Â â€œmoveâ€ in students classssroom interaction of UNRIKA during teaching practice program was the aim of this study. Conversation texts taken froms tudentsâ€™ classssroom interaction of UNRIKA during teaching practice program wereÂ  the data of this research. To analize the data, in this study , descriptive qualitative method was used. There were five classroom interactions selected as the data source. The data were taken by recording then transcripted. Rewriting, Identifing utterences, elaborating and then analized were the process of data analysi. The findings of this study showed that were 261 clauses analysis. There were two types of moveâ€ in students classssroom interaction found, namely congruent and metaphorical â€œmoveâ€ coding. Congruent and metaphorical â€œmoveâ€ coding was 76.63% and metaphorical â€œmoveâ€ coding was 27.37%. Congruent â€œmoveâ€ coding was built in â€œknowerâ€ and â€œactorâ€ analysis, but â€œknowerâ€ analysis was more dominant. It means the conversation texts dominnated by the statement and question, in another word, the content of the interaction refered to the lecturing and discussion situation. Â Keywords: â€œMoveâ€,â€ Knowerâ€, â€œActorâ€ Congruent and Metaphor Coding.